Improving Outcomes for Noncommunicable Diseases in Low- and Middle-Income Countries - Kenneth A. LaBresh (RTI Press, 2016)
Noncommunicable diseases (NCDs) are the main cause of death worldwide. In addition, the incidence, prevalence, and death rates from NCDs are expected to increase in the future. No single discipline can address the issues of prevention, early detection, access to care, and appropriate treatment that are needed to improve outcomes for NCDs; this growing need will require transdisciplinary collaborations. Improving outcomes in NCDs is clearly a difficult endeavor that will require significant efforts. However, previous research and program implementation indicate that improving outcomes for NCDs is an achievable goal. Given the tremendous impact of NCDs on morbidity, mortality, and costs worldwide, there is little doubt that efforts to improve NDC outcomes are much needed. Recognizing the importance of new strategies and interventions addressing NCDS globally, RTI funded the projects described here to assess how the institute's range of expertise could be focused on the reduction of NCDs. The projects described in this book focus on the risk factors or treatment (or both) of one or more of the four NCDs that are responsible for the greatest impact on morbidity and mortality: cardiovascular disease, cancer, diabetes, and chronic respiratory diseases. The pilot projects were carried out in low- and middle-income countries, which are disproportionately affected by NCDs. The lessons learned from these initial pilot projects have great potential to be increased in their scale and reduce the devastating impact of noncommunicable diseases.